ОСОБЕННОСТИ РАЗВИТИЯ ОВРАЖНОЙ ЭРОЗИИ ВО ВРЕМЕНИ В РАЗЛИЧНЫХ ПРИРОДНЫХ УСЛОВИЯХ - Любимов Б.П.; Ковалев С.Н. (My University, 2006)
Diversity of gullies' morphology depends on temporal and zonal peculiarities of their development. Time intervals used in the analysis of their dynamics are the following: 1) phases - diurnal, 2) rhythms - seasonal, 3)periods -annual, 4) cycles - multiannual. The stages of gullies' dynamics are considered according to this time division and geographical zone. This approach should be used for planning and any applied purposes, because the annual average rates are insufficient.
Keywords: 551.435.162